2018
DOI: 10.1155/2018/7843208
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of the Quick Detection of Selectins Using Raman Spectroscopy to Discriminate Lung Cancer Patients from Healthy Subjects

Abstract: This study aimed at determining the concentration of P-selectins in lung cancer patients in different stages and healthy subjects. Then, the ability of the methodology developed to discriminate the existence of lung cancer was also evaluated. Serum spectra were obtained using Raman spectroscopy (RS). Blood samples were taken from subjects divided into two groups: group 1—comparing data from 22 patients clinically diagnosed with cancer before versus after medical intervention; group 2—comparing data from 10 pal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…An increase in P-selectin expression on the surface platelets could be a biomarker in some types of cancer, including breast, lung, kidney, and colon cancers [ 54 , 55 ]. Our current study, as in a previous one [ 56 ], showed that the P-selectin level decreased after surgery and increased in the palliative group. Cardiological medications reduced the level of this adhesion molecule.…”
Section: Discussionsupporting
confidence: 91%
“…An increase in P-selectin expression on the surface platelets could be a biomarker in some types of cancer, including breast, lung, kidney, and colon cancers [ 54 , 55 ]. Our current study, as in a previous one [ 56 ], showed that the P-selectin level decreased after surgery and increased in the palliative group. Cardiological medications reduced the level of this adhesion molecule.…”
Section: Discussionsupporting
confidence: 91%